Fragmentos de la vida y obra de Unica Zürn - Martínez Díez, Noemi (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2007)
The aim is present a panoramic vision of the life and work of Unica Zürn, her childhood and youth in Berlin, her encounter with H.B., period of her important creations, illness and tragic end.
Keywords: Firsts years; Bellmer; Schizophrenic